2015
DOI: 10.1016/j.nima.2015.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation properties of solution-grown trans-stilbene single crystals

Abstract: The scintillation properties of trans-stilbene crystals grown for the first time by application of the solution growth technique to the scale of 10 cm are reported. Measurements of the scintillation light output, pulse shape discrimination, and neutron detection efficiency were made with sets of crystals cut as 50 cm diameter cylinders of different lengths from 0.3 to 10 cm. Comparison to liquid scintillators and traditional melt-grown stilbene showed that at increasing sizes new solution-grown crystals exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 21 publications
0
60
0
Order By: Relevance
“…We suggest that the measurement results presented here are representative of the fact that some sources (in the subset of shielded Pu threats) could be visible while moving only through use of the fast neutron counting modality. This work implies that the addition of fast neutron counting, especially considering a brighter organic scintillator like stilbene [13], may add value for mobile detection of shielded Pu. The full-scale mobile system proposed here, although expected to add capability, is quite complex, expensive, and heavy.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the measurement results presented here are representative of the fact that some sources (in the subset of shielded Pu threats) could be visible while moving only through use of the fast neutron counting modality. This work implies that the addition of fast neutron counting, especially considering a brighter organic scintillator like stilbene [13], may add value for mobile detection of shielded Pu. The full-scale mobile system proposed here, although expected to add capability, is quite complex, expensive, and heavy.…”
Section: Discussionmentioning
confidence: 99%
“…The crystalline organic scintillator trans-stilbene (hereafter referred to as stilbene) has attracted renewed interest for radiation detection applications [1][2][3] due to the recent development of a solution-based growth method that enables the fabrication of large monocrystals with excellent neutron-gamma pulse shape discrimination (PSD) and high light output [4][5][6]. Stilbene, like many crystalline organic scintillators, exhibits an anisotropic scintillation response to heavy charged particles; the response is dependent on the charged particle trajectory with respect to the crystalline axis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Carman et al [9] and Zaitseva et al [10] showed that high-optical quality crystals of stilbene can be grown to a 10-cm scale from solution. Some current and future applications may require larger size and quantity of crystals, production of which can be a complicated task without detailed knowledge of the growth mechanisms and structure, to avoid formation of defects harmful for the final application.…”
Section: Introductionmentioning
confidence: 99%